Company tax - effective tax rates on profits - Stewart, J. C. (Statistical and Social Inquiry Society of Ireland, 1981)
Considerable controversy surrounds the measurement of profit in company accounts. Continuous inflation has underlined some of the problems involved. Current accounting practice in the United Kingdom and Ireland also obscures the amount of direct tax that companies pay. Kay and King (1980, p. 193) comment that the "effect of this accounting practice is that many companies, especially in manufacturing industry, show substantial tax charges in their accounts when in fact they are paying little or no tax at all". A similar comment applies to Irish companies as accounting standards in Ireland follow closely those in the United Kingdom. In addition, many features of United Kingdom Finance Acts are incorporated into subsequent Irish Finance Acts. A combination of differing or controversial measures of profit and obscure reporting of tax paid makes the calculation of tax rates on profits for the corporate sector a difficult if not arbitrary process.
Read before the Society, 2 April 1981
Keywords: Company tax; Inflation; Effective tax rates; 314.15